(3TQM efXheI GHf SjfG aj GdWHs - (3CHh RjO YHO GdQMef Hf CHi LeYIs; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdaGVd hdi Yde GdQFjS , CHh RjO YHO GdQMef GHf GdTjN GdaGVd GdMSjH GdeJWHH CHh LeYI (B: (3GdLRAGdKGfi ef GdCQLhRI , hgh GdYedi hJbSjeg hEP fXeJ ai cJGH GdYde ai GdWH eG CSeYJg ef fXe s
(3BNQgG (B:s
(3Ke jdRe UGMHg JScjf Pdc GdYVh , dCbd ef TgQ , hQHeG GMJjL Edi Cf jHbi YTQkG HYO GdTgQ , CYfi CQHYjf jhekG s
(3ai ChdgG Jedjc dCHi GdYdGA Hf CHj LeYIs
(3hGfXQ TQM CQLhRI GHf SjfG ai GdWH Qbe (B35(3,(B36(3,(B573-540"s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
Keywords: (3GdWHs